Experiential learning in architectural education : design-build and live projects - Pak, Burak; De Smet, Aurelie (Abingdon, Oxon : Routledge, 2023)
"This book is designed to be of interest to many different audiences due to its cross-sectoral and transdisciplinary content. It will appeal to those within architectural higher education as well as to spatial practitioners, students, civic and governmental organizations engaged in socio-spatial projects. The book is (1) an academic source of critical and practice-driven knowledge on experiential architectural design learning (2) provides methods for other ways of learning in the form of design-build and live projects and (3) offers design inspiration for community-engaged spatial practices relevant to both educators and practising architects and designers"--
Inspiring public imagination through a micro ecovillage for students / Cameron Van Dyke -- Co-creating urban strategies through trans-local learning alliances / Catalina Ortiz.
Keywords: Architecture -- Study and teaching; Experiential learning; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Study & Teaching